ANALYSIS OF LOCAL WISDOM TOWARD ENVIRONMENTAL CONSERVATION ATTITUDE IN BANGKALAN DISTRICT: A PRELIMINARY RESEARCH - Yunin Hidayati (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
Based on the results and discussion previously described, the results can be concluded that local wisdom in Bangkalan district can be used to raise awareness of the importance of environmental conservation and the use of potential around the community. Suggestions that can be given is that it expected that research is developed for implementation in the field of education by including into one of the learning materials for example on the topic of environmental pollution.